Association of Vitamin D, Zinc and Selenium Related Genetic Variants With COVID-19 Disease Severity - Kotur, Nikola; Skakic, Anita; Klaassen, Kristel; Gasic, Vladimir; Zukic, Branka; Skodric-Trifunovic, Vesna; Stjepanovic, Mihailo; Zivkovic, Zorica; Ostojic, Olivera; Stevanovic, Goran; Lavadinovic, Lidija; Pavlovic, Sonja; et al. (Frontiers in Nutrition, 2021)
Background: COVID-19 pandemic has proved to be an unrelenting health threat for more than a year now. The emerging amount of data indicates that vitamin D, zinc and selenium could be important for clinical presentation of COVID-19. Here, we investigated association of nutrigenetic markers of vitamin D, zinc and selenium with clinical severity of COVID-19. Methods: We analyzed variants in genes significant for the status of vitamin D (DHCR7/NADSYN1rs12785878, GC rs2282679, CYP2R1 rs10741657, and VDR rs2228570), zinc (PPCDC rs2120019) and selenium (DMGDH rs17823744) in 120 Serbian adult and pediatric COVID-19 patients using allelic discrimination. Furthermore, we carried out population nurigenetic study among European and other worldwide populations to investigate variation in allelic frequencies. Results: Study showed that DHCR7/NADSYN rs12785878 and CYP2R1 rs10741657 variants were associated with severe COVID-19 in adults (p=0.03, p=0.017, respectively); carriers of DHCR7/NADSYN TT and CYP2R1 GG genotypes had 4.9 and 5.9 times higher risks for severe disease, OR 4.9 [1.1-20.1] and OR 5.9 [1.4-25.2], respectively. There were no associations between selected genetic variants and disease severity in pediatric patients. Population nutrigenetic study revealed that Serbian population had the lowest frequency of CYP2R1 rs10741657 G allele compared to other non-Finish Europeans (0.58 compared to 0.69 and 0.66 in Spanish and Italian population, respectively), suggesting that other populations should also investigate the relationship of CYP2R1 variant and the COVID-19 disease course. Conclusion: The results of the study indicated that vitamin D related nutrigenetic markers were implicated in severe COVID-19 in adults. This could direct prevention strategies based on population specific nutrigenetic profiles.